Friction stir welds with enhanced fatigue strength and life post laser peening - Antunes, Joana; Ganguly, Supriyo; Irving, Phil E.; Furfari, Domenico; Busse, David; Pacchione, Marco (Elsevier, 2023)
This study aims to quantify the influence of laser peening on the structural integrity of a FSWelded aluminium fuselage joint. Fatigue tests with different stress amplitudes were performed for samples in as-machined and friction stir welded conditions to characterise the loss of fatigue strength and the effect of stress amplitude on the degradation of fatigue life. Optimisation of laser parameters was carried out to achieve an appropriate through-thickness stress profile. The optimised parameters were used to peen tensile coupon specimens and analyse the fatigue life recovery. The residual stress fields were quantified using the central incremental hole drilling method on peened and unpeened samples. It was found that both the microstructure and superposition of residual stresses from the welding process and peening treatment play a crucial role in the fatigue behaviour of the FSWelded joint. Using the parameters and layout described in this article, laser peening was able to increase the fatigue life of as-welded samples by a factor of 2.4 for the lower end of the load spectrum tested. This represents a recovery of 65% when compared to the pristine aluminium reference samples.
Keywords: fatigue; joints; friction-stir-welding; laser peening; residual stresses